Functional outcome of galeazzi fracture dislocation treated by open reduction and internal fixation with dynamic compression plate - Kumar, Manoj; Kumar, Amit; Gupta, Sanjeev; Mahajan, Neeraj; Lone, Zubair A.; Ahmed, Maneer (International Journal of Research in Medical Sciences, 2021)
Background: Galeazzi fracture involves fracture of the distal 1/3rd of radius shaft associated with dislocation of distal radioulnar joint. Open reduction and rigid internal fixation of radius is goal standard treatment. The aim of this study was done to evaluate the functional outcome of Galeazzi fracture dislocation managed by open reduction and internal fixation of radius. Methods: The study was conducted in department of orthopaedics Government Medical college Jammu from December 2018 to February 2021. 30 patients of Galeazzi fracture dislocation were managed with Open reduction and internal fixation of Radius with plating and were followed up to evaluate the results. Results: Age of the patients ranged between 23 years to 60 years with a mean range of 42 years. 22 cases were male (73.3%), 8 cases were females (26.6%). In 19 cases injury was in right side and in 11 cases injury was in left side. In most of the cases injury was due to due to RTA (80%) and in rest of cases injury was due to fall from height (20%). Conclusions: Anatomic restoration of length of the radius with rigid internal fixation is key to satisfactory results in Galeazzi fracture dislocations and K-wire fixation of distal radio ulnar joint is not necessary if anatomic reduction of the joint is obtained by indirect means such as open reduction and internal fixation of the radius and immobilization.